Implementing Diagnostic Assessment in Designing Differentiated Learning for English Language Learning at the Junior High Schools - Badrun Kholid; Arif Rahman; Lalu Ari Irawan (Lembaga Penelitian dan Pemberdayaan Masyarakat (LITPAM), 2024)
The Merdeka Curriculum is an educational framework in Indonesia that emphasizes core subjects, personality development, and student skills. It integrates various assessments, including diagnostic, formative, and summative, to tailor education to individual student needs. Diagnostic assessments, in particular, are used to identify students' strengths and weaknesses, facilitating personalized learning experiences. Therefore, this study focuses on the implementation of diagnostic assessments in designing differentiated learning modules for English language learning in junior high schools in East Lombok. The purpose of this study is to investigate how teachers use diagnostic assessments to identify students' learning profiles, interests, and readiness, and how they subsequently design and implement differentiated teaching modules. This qualitative study involves interviews and observations with teachers who are implementing the Merdeka Curriculum. Data were collected through participatory observations and in-depth interviews to understand the practical application. The study revealed that teachers use three main tools for diagnostic assessment: the Quizizz application, the Akupintar.id website, and questionnaires. These tools help identify students' learning profiles and interests at the beginning of the school year. The research also identified five steps to develop differentiated learning modules: assessing students' needs, setting learning objectives, designing learning activities, incorporating different learning styles, and conducting regular formative assessments. Additionally, seven steps were found to be crucial for implementing differentiated learning, including classroom layout, use of varied learning materials, flexible teaching approaches, and regular assessment and feedback. The study can be concluded that the implementation of diagnostic assessments in the Merdeka Curriculum significantly aids in designing effective differentiated learning modules. This approach helps cater to individual student needs, enhancing their learning experiences and outcomes.